Ethanol: uma plataforma SDN para redes wi-fi - Henrique Duarte Moura (2015)
Wireless networks are common in most enterprise environments, as well as in homes with broadband Internet access. To support mobile users growing demand, we noticed a tendency to reduce the coverage area of an access points wireless signal while the number of these devices increases. Several proprietary solutions seek to solve the problems arising from the densification of access points, such as increased interference and greater amount of stations roaming among acess points changing antennas. The introduction of a new network device, the devices maintenance or correcting problems in an existing device makes the administrator work tedious and error prone, because that requires the reconfiguration of each of the numerous network nodes. The management of network stations is painful for network administrators, which suffer from a lack of interoperability between different manufacturers solutions and fail to obtain solutions tailored to their needs. Software-defined networking (SDN) is an approach to computer networks that allows us to manage it through an abstraction in which the system that makes decisions about the data flow (control plane) is decoupled from the underlying systems that forward data (data plane). Current SDN solutions, that use the OpenFlow protocol, are insufficient to deal with the dynamicity of wireless networks, their security needs and their aspects of quality of service (QoS). To improve the performance of these networks requires new approaches, which are not possible in commercial WLAN (Wireless local area networks) controllers, since they are proprietary and closed. One solution is to use open APIs that enable the development of applications and context sensitive control algorithms. In this Masters thesis we propose an SDN architecture for wireless networks based on IEEE 802.11, called Ethanol, whose API allows the development of custom control software. Ethanol refactors the control and data plane functionalities between wireless access points and the SDN controller without changing the wireless stations. This centralized controller, which has a global view of the network, operates the wireless APs, controlling the quality of service in the links, client mobility and the process of association and disassociation of wireless stations as well as other wireless links parameters. Using the Ethanol architecture we create an Ethanol access point prototype, whose operation and performance were evaluated on four case studies involving quality of service, client association control, suppression of ARP packets and identification of problems at the wireless interfaces. Our case studies results show that the approach of software defined wireless networks is feasible, and SDN allows to act upon various management problems of dense wireless networks. As future work, we propose to extend Ethanol to comply with other IEEE protocols proposed to assist the operation of 802.11 networks when these protocols are implemented in the 802.11 drivers, and also test it under a mesh network.